Aktualisasi Komitmen Beragama Waria Kota Kediri - Reza Ahmad Zahid (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2020)
The existence of transgender in social life still leaves many problems. Negative stigma and discrimination are already firmly attached to them. This problem certainly requires handling so that the negative mindset of transgender women does not only put to something horrible in nature. They also cannot be separated from their natural tendency as religious humans (homo-religious). This study seeks to reveal the religiosity side of transgender women and how they actualize their religious-selves. Because of this reason, the researcher uses the concept of Maslow as self-actualization, then Stark and Glock as religious commitment in the framework of qualitative-phenomenological research. In-depth interviews, observation, and documentation are techniques in extracting data, then analyzed inductively. The results of this study found that the fact, transgender religious behavior fulfills the five dimensions of religion as per the conceptual framework of Stark and Glock as religious commitment. Second, the self-actualization of transgender women in their religious-life also shows that they have an inner need through Nurul Iman jamiyyah. They follow recitation consistently where the senior transgender (adult) has moved to religious maturity that manifested in their daily life by the religious commitment and always follow jamiyyah, and encourage younger transgender women to keep trying to carry out religious-teachings.